'Capricho' Avoiding Fear in Encounters with Spirits in the Andes - OSCAR Munoz (Etnografia Polska)
This article analyses encounters of Quechua peasants in the Potosí region of Bolivia with sajra espíritus (evil spirits). In order to ensure that these spirits do not cause them too much harm, they must not be afraid and this fearless state is achieved by means of what they call capricho. This word refers to a set of courageous actions during the encounter, which mainly allow the waylaid person to recognise the spirit and therefore to know how to deal with it. But this whole process must be shared and verbalised. Thus, capricho extends beyond the event and is also present in the transmission of the experience.